Effects of altitude training on heart rate variability in orthostatic test in elite swimmers - Hynynen, E.; Iglesias, X.; Feriche, B.; Calderon, C.; Abalos, X.; Vazquez, J.; Barrero, A.; Rodriguez, L.; Levine, B. D.; Rodriguez, F. (Sport Science Research Group, INEFC-Barcelona, 2012)
Different stressors, like athletic training, can change the autonomic modulation of the heart. This can be evaluated with heart rate variability (HRV) analysis. Acute hypoxia is also known to attenuate parasympathetic activity and accentuate the sympathetic activity. Whether these changes in autonomic modulation will disappear with altitude acclimatization remains unclear. PURPOSE: This study was made to investigate the effects of 3-week moderate altitude training on HRV in elite swimmers. METHODS: 9 elite swimmers (Hi) of international level (5 women and 4 men, age 19.4 ± 1.6 years) lived and trained 3 weeks at Sierra Nevada, Spain (2,320 m). Control group (Lo) consisted of 11 swimmers of similar level (7 women and 4 men, age 17.9 ± 1.9 years), who lived and trained at sea level. RR-intervals were recorded every morning in supine (8-min) and orthostatic (6-min) positions with beat-by-beat heart monitors. Breathing was paced to 12 breaths/min. Recordings were done during the 3-week intervention period and one week before and after. HRV was analyzed from the last 5-min period of both positions with FFT spectral power analysis. TRIMPs of every training session were calculated to estimate training load. HRV results are averaged over every week and presented as relative percentage changes. RESULTS: The training load was similar in both groups during the 3-week intervention but was lower during the week after in Hi-group when compared to Lo-group (P=0.003). An interaction of group, time and TRIMPs was found in change in spectral power of supine LF (-40% vs. +36%, P=0.02) and HF (-46% vs. +55%, P=0.01) during the intervention period showing increased HRV in Lo group and decreased HRV in Hi-group. Also LF (+93% vs. +12%, P=0.01) and LF/HF ratio (+79% vs. -2%, P=0.01) during standing increased more in Hi-group than in Lo-group in the end of the intervention. CONCLUSION: The present findings of lower HRV in Hi-group than in Lo-group suggest that the physiological stress of training at moderate altitude leads to parasympathetic withdrawal and possibly increased sympathetic activity even after night rest. Thesechanges in autonomic modulation seem to last longer than for the first week after altitude training camp.